Embodied learning on the network: Experiences from the field - Kehrwald, Benjamin A. (Proceedings of the International Conference on Networked Learning, 2014)
For many, if not most, professions, practice is embodied. Embodied learning associated with embodied professional practice poses a number of challenges for networked educators working in professional degree programs. The consideration of embodied learning forces a shift from a focus on cognitive, ’in the head’ learning, to a more holistic view which includes whole body experiences, embodied practice and embodied cognition. This shift calls into question the ways learning is defined and the means by which learning is structured, facilitated, supported and assessed within educational programs. These questions can be difficult to address in networked learning situations where the physical has been supplemented or replaced with the virtual, where participant experiences are mediated by technology and in which good practices in learning design and facilitation are less well established. The purpose of this paper is to provide a basis for understanding embodied learning and the ways in which it may be supported and facilitated in networked learning situations. This paper provides the conceptual foundations of a continuing project on the design and development of networked courses which support embodied learning. The paper is structured in three parts. The first part provides background through a description of embodied learning and its links to professional practice. The case in point is an initial (pre-service) teacher education program at the University of South Australia. The second part identifies commonalities between networked learning and embodied learning with reference Goodyear’s (2002) framework for understanding ‘good learning’ as active, cumulative, individual, self-regulated and goal-oriented. The third part draws upon recent experiences designing and developing networked courses within a teacher education program at The University of South Australia. The discussion identifies challenges associated with practical work to design, develop and implement embodied learning including a) explicitly identifying intended learning outcomes associated with embodied learning; b) the relationship between ‘real’ (embodied, physical) and ‘virtual’ aspects of the learning experience; c) identifying appropriate learning environments for embodied learning; d) providing access to necessary physical artefacts to support embodied learning and e) creating records of performance as part of the learning (and assessment process). The discussion includes in-context responses to those challenges and a list of tentative conclusions which guide ongoing work related to these challenges.